1985
DOI: 10.1159/000173042
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Effect on Renal Function of Normotensive and Hypertensive Rats

Abstract: The effect of verapamil, a Ca++ antagonist drug, on renal function and proximal fluid reabsorption in normal and hypertensive (GΠ) rats was studied. During intravenous infusion of verapamil, mean arterial pressure (MAP) fell significantly in both groups, 23% more in hypertensive than in normotensive rats. Glomerular filtration rate (GFR) was significantly higher in hypertensive rats and also increased significantly in this group during verapamil infusion. Effective renal plasma flow (ERPF) was simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Nevertheless, in a micropuncture experiment, MacLaughlin et al 39 observed that 10" 5 M verapamil added to the luminalfluid perfusate of normal Wistar rats produced a 36% decrease of sodium reabsorption and that a greater reduction (61%) of sodium reabsorption occurred when verapamil was infused into peritubular capillaries. Similarly, Figueiredo et al 40 found a significant decrease of sodium reabsorption in isolated perfused proximal tubules of rabbits when verapamil was added to the bathing solution in a concentration of 5 /nmol/dl.…”
mentioning
confidence: 99%
“…Nevertheless, in a micropuncture experiment, MacLaughlin et al 39 observed that 10" 5 M verapamil added to the luminalfluid perfusate of normal Wistar rats produced a 36% decrease of sodium reabsorption and that a greater reduction (61%) of sodium reabsorption occurred when verapamil was infused into peritubular capillaries. Similarly, Figueiredo et al 40 found a significant decrease of sodium reabsorption in isolated perfused proximal tubules of rabbits when verapamil was added to the bathing solution in a concentration of 5 /nmol/dl.…”
mentioning
confidence: 99%
“…Consis tent with these findings, a previous in vivo micropuncture study in the rat demonstrated that the renal interstitial in fusion of 10 5 M PGE2 significantly stimulated proximal so dium reabsorption [6]. Additionally, a previous in vivo mi croperfusion study showed that 10 ' M verapamil added to the luminal fluid perfusate markedly decreased proximal sodium reabsorption [9], Therefore, the renal interstitial in fusions of verapamil and PGE: have opposing effects on so dium reabsorption by the proximal tubule of the rat.…”
Section: Discussionmentioning
confidence: 56%
“…18 observed that 5-10 mol verapamil added to the luminal perfusate of normal Wistar rats caused a 36% decrease of Na reabsorption. When verapamil was infused into the peritubular capillaries a greater reduction of 61% of Na reabsorption occurred.…”
Section: Discussionmentioning
confidence: 96%